Prognostic value of structural chromosomal rearrangements and small cell clones with high hyperdiploidy in children with acute lymphoblastic leukemia - Zemanova, Zuzana; Michalova, Kyra; Sindelarova, Lenka; Smisek, Petr; Brezinova, Jana; Ransdorfova, Sarka; Vavra, Vladimir; Dohnalova, Alena; Stary, Jan (Leukemia research, 2005)
In this study, 107 children with acute lymphoblastic leukemia (ALL) were analysed for the presence of hyperdiploidy by cytogenetics and interphase fluorescence in situ hybridisation (I-FISH). Structural aberrations in hyperdiploid cells were investigated by multiple colour FISH (mFISH). Clones with high hyperdiploidy (>50 chromosomes) (HeH) were found in 46 patients (43%). In nine of these (20%), the abnormal clone was present in <20% of the total cell population. There was no significant difference in EFS between those patients with HeH in 2.5-20% or >20% of cells. Structural rearrangements in the HeH clone were found in 10 patients (22%). In this study, HeH karyotypes containing structural aberrations were an indication of a poor prognosis in childhood ALL.
Keywords: DNA, Neoplasm; buněčné klony; průtoková cytometrie; hybridizace in situ fluorescenční; kojenec; Prognosis; mladiství; akutní lymfatická leukemie; mužské pohlaví; Infant; dítě; In Situ Hybridization, Fluorescence; Child; Flow Cytometry; Child, Preschool; ženské pohlaví; prognóza; Humans; předškolní dítě; Chromosome Aberrations; DNA nádorová; chromozomální aberace; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Clone Cells; Female; Adolescent; lidé; Male